An Overview on Peaceful & Enlightening Neurobics: Improving Memory Retention in the Elderly with Neurobic Exercise (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The target of this Quasi-exploratory research was to analyze the impact of Neurobic Exercise on the Memory Enhancement in the Elderly individuals experiencing Dementia. In the midst of January to September 2012, twenty two female more seasoned adults experiencing dementia who were living at Mitraparpsongkoh Foundation, Pathum Thani Province in Thailand, were purposively chosen to take an interest in this examination. Chosen individuals were associated with Neurobic Exercise Program on each 2 days reliably for about a month. The instruments comprised of a Demographic Data Form, the Mini-Mental State Examination-Thai 2002, the Memory test and a Neurobic Exercise Program. The unwavering quality of the Mini-Mental State Examination -Thai 2002 and the memory test using Kuder-Richadson 20 were.89 and 81 individually. Information was examined using unmistakable bits of knowledge and Paired t-test. The outcomes uncovered that the normal memory scores of the exploratory assembling in the wake of getting the Neurobic Exercise Program were accurately and basically higher than before accepting the Neurobic Exercise Program at a dimension of p < .001. The aftereffects of this examination could be utilized as rules by human services suppliers in upgrading the memory maintenance of the elderly individuals experiencing dementia and deferring the crumbling of the cerebrum.